Pendampingan Digitalisasi Pembuatan Laporan Keuangan Rumah Tahfidz Sholeh dalam Transparasi Laporan Keuangan Kas berbasis Website - Khaerul Anam; Asep Sumantri; Niken Harsanti (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
Guidance on the use of digital technology is needed to produce relevant, effective, and efficient financial reports. The mentoring method is carried out in several stages. The first stage is the initial stage through observation, compiling mentoring materials, and preparing facilities and infrastructure. Second, the implementation stage involves socialization and direct practice in the form of training on the use of website-based applications, starting from recording daily transactions to creating more structured financial reports. This activity is motivated by the importance of transparent, accountable, and efficient financial governance in religious institutions, particularly Rumah Tahfidz. Through this training, managers and administrative staff will be trained to create a digital financial reporting system using a web-based platform that is easy to access and use. The expected results of this activity are the realization of a transparent and efficient web-based financial reporting system, increased digital competence of Rumah Tahfidz managers, and growing awareness of the importance of digitalization in the management of religious institutions. The transaction recording process becomes more structured, efficient, and can be done in real time, thus enabling more accurate and up-to-date financial monitoring.